(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The purpose of the article is to study the effect of bath procedures on the body of athletes as a means of recovery and improvement of working capacity. Methods. Analysis, generalization, systematization of scientific research data and literary sources. The results. The article examines the problematic issues of the influence of bath procedures on the body of athletes as a means of recovery and increasing work capacity, the effect of bath procedures on thermoregulation, the central nervous system, the cardiovascular system, the function of external respiration, the neuromuscular apparatus, the skin and body weight, energy metabolism and metabolism, in particular, the impact of various types of bath procedures on the individual characteristics and reactions of the athlete is highlighted. Rest and recovery allow the body to adapt to loads, which contributes to the improvement of physical fitness and training efficiency in the future. It should be remembered that the recovery of working capacity in the training process of athletes is no less important stage than the training itself and requires a comprehensive approach, including rest, proper nutrition, regular sleep, massage, bath procedures and other recovery methods. Conclusions. The conducted research showed that it is important to take into account the individual characteristics and needs of each athlete when developing a recovery program. Coordination with coaches, physical therapists, and other professionals can help ensure effective rehabilitation of athletes. However, it is important to take into account that the use of bath procedures should be careful and take into account the individual characteristics of the athlete, his physical condition and the general level of stress.